Effectiveness of Using the Congklak Game in Improving the Numeracy Skills of Grade 1 Elementary School/MI Students - Widiya Putri, Fika; Dahlan, Zaini (Edumaspul: Jurnal Pendidikan, 2023)
One unique component that contributes to an individual’s intellect is their capacity for calculation. The Congklak game is one of the most useful educational tools for helping primary school pupils improve their numeracy abilities. An ancient game that continues to rise in popularity in Indonesian society is congklak. This kind of research uses experimental methodologies and is quantitative in nature. Pre Experimental Designs is the design that was employed in this study. One Group Pretest-Posttest Design is the type of pre-experimental design that is employed. A significant value (p) of 0.000 < 0.05 was found for the Paired Sample T-Test analysis, yielding a value of t = -11.730. This demonstrates that class I students at SDN 22 Bilah Hulu had a different average numeracy ability before and after receiving learning materials in the form of the classic game congklak. After receiving learning materials in the style of the classic Congklak game, students’ average numeracy skill is higher than it was prior to receiving the conventional Congklak game learning materials. This study demonstrates the efficacy of the classic Congklak game learning resource in raising primary school students’ numeracy proficiency.